An EFL Teacher Perspective on Implementation of Dual Curriculum (Cambridge and Indonesian K13 National Curriculum) at Mutiara Persada School, Yogyakarta - RUDHA WIDAGSA (Journal of English Language Teaching and English Linguistics, 2022)
The aim of this research is to find out the problems and the strategies of the EFL teacher on the implementation of Cambridge and national curriculum (k13) at Mutiara Persada school of Yogyakarta. This research is conducted based on the difficulties encountered by EFL teacher in the implementation of Cambridge and National Curriculum on fourth grade of Mutiara Persada Elementary School of Yogyakarta. This research adopted a qualitative research design. This type of problem was dealing with personal struggle of the EFL teacher when teaching using the two curricula in an international class. The struggle could be psychological, technical, or just simply lack of knowledge in the field. Those kinds of problem would be appropriate if approached using personal interaction such as deep interview. The result of this research found that the most common problem was not from the teacher’s background of study which in this research is EFL teacher. However, the problem comes from how the teacher adapted to the both of curriculums. Instead, the EFL teacher has better understanding of English terms that are used in Cambridge textbook. Teacher with English background also has better understanding in viewing the students’ skill which in turn the teacher knows how to adapt themselves with the student’s capacity. EFL teacher also has benefit in teaching global mindset to the student which is part of Cambridge curriculum’s goal. The researchers also find out the strategy that the teacher used which is once that the terms are understood then the problem was to make the students understand that the term in Indonesian and in English is similar in meaning, only different in language. Since teaching young learners only uses a simple terminology, not the complex one, the only adaptation that the teacher made was only in the terms used.